Cecocolic intussusception and cecal torsion in cattle - Da Conceição, Ângela Imperiano; Silva, José Ricardo Barboza [UNESP]; De Alcantara, Uila Almeida Aragão; De Mendonça, Carla Lopes; Coutinho, Luiz Teles; De Paula Cajueiro, Jobson Filipe; Souto, Rodolfo José Cavalcanti; Afonso, José Augusto Bastos (My University, 2021)
This work aims to describe the clinical, laboratory, and anatomopathological findings of two bovines, one affected by cecocolic intussusception, and the other by dilation with cecal torsion. The clinical examination demonstrated metallic resonance from the right flank, ruminal and intestinal hypomotility, and abdominal distension, in addition to alterations in feces characteristics. Was observed in the two animals leukocytosis by neutrophilia with regenerative shift to the left, and hyperfibrinogenemia. The analysis of ruminal fluid revealed impairment of the microbiota and an increase in chloride levels. The laparoscopic examination performed on one of the animals showed dilation of the colon, the cecum with hyperemia and serous edema, with a dividing halo between affected and unaffected portions, in addition to reddish peritoneal fluid. In the laparotomy, an enlarged cecum was found, with gaseous and liquid contents, swollen and turgid colon, and peritonitis. In addition to the findings observed during surgery, the anatomopathological examination demonstrated, in bovine 01, intestinal intussusception in the region of the cecocolic valve, and, in bovine 02, twisting of the loop at the ileocecocolic junction. Despite the low occurrence of digestive system disorders in cattle, cecal torsion and intussusception represent serious intestinal clinical conditions. These reports take the attention to the importance of a multidisciplinary approach to provide a correct diagnosis of intestinal diseases.
Intussuscepção cecocólica e torção de ceco em bovinos
Keywords: Bowel obstruction; Digestive disorder; Digestive system; Laparoscopy